+0  
 
0
47
1
avatar

Please help with these systems problems.

 

 Jul 30, 2020
 #1
avatar+116 
+1

Well, for substitution, it's very simple:

3x + 6(-5) = -18

3x + (-30) = -18

3x = 12

x = 4

 

Then, for elimination it would be:

(-7x + 9y = -19)

+ (4x -9y = 10)

------------------------

-3x = -9

x = 3

 

And finally, for the other elimination:

(-5x + 8y = -4)

+ (6x - 8y = -12)

---------------------

x = -16

I am not sure if this is the "right" kind of elimination, but it works!

 Jul 30, 2020

30 Online Users

avatar
avatar
avatar